2020
DOI: 10.1210/endocr/bqaa059
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome as a Circadian Coordinator of Metabolism

Abstract: The microbiome is critically involved in the regulation of systemic metabolism. An important but poorly understood facet of this regulation is the diurnal activity of the microbiome. Herein, we summarize recent developments in our understanding of the diurnal properties of the microbiome and their integration into the circadian regulation of organismal metabolism. The microbiome may be involved in the detrimental consequences of circadian disruption for host metabolism and the development of metabolic disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…During the dark phase, direct GABAergic inhibitory signals from the SCN to the PVN inhibit the PVN to pineal gland projections [118,240]. Rhythmicity in melatonin provides essential regulatory control in metabolism; when melatonin synthesis is abolished by pinealectomy, glucose tolerance is impaired and blood glucose rhythmicity is completely lost under ad libitum feeding conditions [241,242]. Thus, the melatonin-mediated regulation of plasma glucose levels is controlled by a delicate balance of glutamatergic and GABAergic pre-autonomic hypothalamic inputs.…”
Section: Melatoninmentioning
confidence: 99%
“…During the dark phase, direct GABAergic inhibitory signals from the SCN to the PVN inhibit the PVN to pineal gland projections [118,240]. Rhythmicity in melatonin provides essential regulatory control in metabolism; when melatonin synthesis is abolished by pinealectomy, glucose tolerance is impaired and blood glucose rhythmicity is completely lost under ad libitum feeding conditions [241,242]. Thus, the melatonin-mediated regulation of plasma glucose levels is controlled by a delicate balance of glutamatergic and GABAergic pre-autonomic hypothalamic inputs.…”
Section: Melatoninmentioning
confidence: 99%
“…Of note, the gut microbiota is also required for the hepatic clock daily oscillations that regulate metabolic gene expression for optimal liver function [102][103][104]. In fact, the liver and gut are in close anatomical and functional relation via the portal vein.…”
mentioning
confidence: 99%
“…Indeed, bioactive molecules produced or transformed by gut microorganisms interact with the host physiology and trigger responses locally and remotely (Michaudel and Sokol, 2020). It was demonstrated that gut microbiota had their own diurnal oscillations in composition and function, and the microbes and their metabolites might be associated with the detrimental consequences of circadian disturbance for host metabolism (Thaiss et al, 2014;Alvarez et al, 2020). Microbiota-generated metabolites bridge the hostmicrobiota interactions and may be essential for human physiology.…”
Section: Introductionmentioning
confidence: 99%
“…2) bile acids, synthesized in the liver from cholesterol and transformed by intestinal microbiota into the secondary bile acids (Sayin et al, 2013); and 3) tryptophan (Try) and its derivatives, including indole, kynurenine, and downstream products [e.g., 5-hydroxytryptamine (5-HT)] (Agus et al, 2018). Several studies have demonstrated interactions between microbial metabolites and circadian rhythms (Alvarez et al, 2020;Matenchuk et al, 2020). However, currently very few studies have examined the global changes in gut microbial metabolites upon circadian rhythm disturbance.…”
Section: Introductionmentioning
confidence: 99%